Body mass index on musculoskeletal pain and physical activity among elderly - Jamaludin, Thandar Soe Sumaiyah; Firdaus, Mohd Khairul Zul Hasymi; Hashim, Fatin Hanani; Saidi, Sanisah; Chan, Chong Mei (Scholars Academic and Scientific Publishers, 2018)
The rate of obesity has increased in over the years and has become one of the leading causes of morbidity and mortality in Malaysia. It can be said that overweight and obesity are a current trend in our public health problem. Therefore, it increases the risk factor for other problems such as musculoskeletal pain and low physical activity which lead to poor quality of life. This was a cross-sectional by applying of simple random sampling method. There were 372 participants involved in this study and majority of them (51.9%) were overweight. For gender, about 63.7% were female and 36.3% were male. Mostly of the participants were between 60 to 64 years old range (53.2%). Based on the findings, the result showed that there was significant association between age, gender and BMI on the level of musculoskeletal pain. On the other hand, only age showed that there was significant difference on level of physical activity. Majority of the respondent who had overweight BMI experienced musculoskeletal pain. Thus, the healthcare provider especially nurse should plan effective interventions to overcome these problems so that our elderly population will have better quality of life.